Global, Regional, and National Disease Burden and Prediction Analysis of Colorectal Cancer Attributable to Tobacco, Alcohol, and Obesity From 1990 to 2030 - Deng, Yuqi; Wang, Yajie; Yang, Jinsai; Luo, Xinyu; Qiu, Jieya; Long, Rou; Zhang, Chaohui; Li, Jiale; Tang, Guiyang; Chen, Lili; Zuo, Jianhong (Frontiers in Oncology, 2025)
BackgroundColorectal cancer (CRC) ranks among the highest in incidence and mortality rates globally. A significant portion of Colorectal cancer cases and deaths can be attributed to modifiable risk factors, with smoking, alcohol use, and high body mass index (BMI) being the three most prominent. However, the impact of these risk factors on Colorectal cancer across regions, genders, and age groups remains insufficiently characterized.MethodsUtilizing data from the Global Burden of Disease (GBD) study 2019, restrictive cubic splines (RCS) and quantile regression analyses are applied to explore the relationship between the Socio-Demographic Index (SDI) and ASMR or ASDR. Additionally, gender differences, changes across different SDI levels, and age group trends in smoking, alcohol use, and high BMI over the 30-year period are analyzed. The Bayesian age-period-cohort (BAPC) model is employed to predict mortality trends from 2020 to 2030, aiming to explore the epidemiological and sociodemographic transitions in the Colorectal cancer disease burden attributed to smoking, alcohol use, and high BMI.ResultsIn 2019, the number of colorectal cancer deaths globally attributable to risk factors as smoking, alcohol consumption, and obesity increased to 142,931, 52,495, and 85,882 cases respectively, collectively accounting for approximately one-third of all Colorectal cancer-related deaths. Notably, there is an upward trend in early-onset Colorectal cancer mortality associated with these factors.DiscussionTo reduce the burden of Colorectal cancer, it is recommended to enhance health education, promote smoking cessation and alcohol moderation, and increase the coverage and participation in Colorectal cancer screening, which are crucial for lowering Colorectal cancer mortality rates. These findings are vital for the development of public health policies and intervention measures to reduce the global disease burden. They provide guidance for Colorectal cancer prevention across different regions, genders, and age groups worldwide.